PANDANGAN HUKUM ISLAM TERHADAP PERCERAIAN MELALUI MEDIA ELEKTRONIK - Mukhlis Effendi (The Juris, 2020)
This study analyzes the views of Islamic law on divorce through electronic media. A new problem that requires a comprehensive review to provide certainty of Islamic law without leaving the teachings of the Qur'an and Sunnah that has been outlined by Allah SWT. However, in the development of increasingly sophisticated technology, it is easier for anyone to divorce his wife, one of which used to be known as divorce by letter or writing, so now it can be easier and faster to get to the target, namely the husband, who only by doing sending written messages remotely by means of electronic media in the form of mobile phones/electronic media. With this, the legitimacy of the fall of divorce invites pros and cons for the community.